Human adipose tissue as a major reservoir of cytomegalovirus-reactive T cells - Redruello-Romero, Anaïs; Benitez-Cantos, Maria S.; Lopez-Perez, David; García-Rubio, Jesús; Tamayo, Francisco; Pérez-Bartivas, Daniel; Moreno-SanJuan, Sara; Ruiz-Palmero, Isabel; Puentes-Pardo, Jose D.; Vilchez, Jose R.; López-Nevot, Miguel Á.; García, Federico; et al. (Frontiers in Immunology, 2023)
Cytomegalovirus (CMV) is a common herpesvirus with a high prevalence worldwide. After the acute infection phase, CMV can remain latent in several tissues. CD8 T cells in the lungs and salivary glands mainly control its reactivation control. White adipose tissue (WAT) contains a significant population of memory T cells reactive to viral antigens, but CMV specificity has mainly been studied in mouse WAT. Therefore, we obtained blood, omental WAT (oWAT), subcutaneous WAT (sWAT), and liver samples from 11 obese donors to characterize the human WAT adaptive immune landscape from a phenotypic and immune receptor specificity perspective. By high-throughput sequencing of the T cell receptor (TCR) locus, we found that tissue TCR repertoires are less diverse and dominated by hyperexpanded clones compared to blood samples. Additionally, we predicted the presence of TCRs specific to viral epitopes, particularly from CMV, which was confirmed by ELISpot assays. Moreover, we found that oWAT has a higher proportion of CMV-reactive T cells than blood or sWAT. Finally, flow cytometry showed that most WAT-infiltrated lymphocytes were tissue-resident effector memory CD8 T cells. Overall, these findings postulate human oWAT as a major reservoir of CMV-specific T cells, presumably for latent viral reactivation control.